2015
DOI: 10.1128/aem.04038-14
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Involved in Fe(III) Respiration by the Hyperthermophilic Archaeon Ferroglobus placidus

Abstract: The hyperthermophilic archaeon Ferroglobus placidus can utilize a wide variety of electron donors, including hydrocarbons and aromatic compounds, with Fe(III) serving as an electron acceptor. In Fe(III)-reducing bacteria that have been studied to date, this process is mediated by c-type cytochromes and type IV pili. However, there currently is little information available about how this process is accomplished in archaea. In silico analysis of the F. placidus genome revealed the presence of 30 genes coding for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 73 publications
(90 reference statements)
2
31
0
Order By: Relevance
“…The putative function of outer-surface cytochromes is terminal electron transfer to extracellular electron acceptors, similar to the role that outer surface c -type cytochromes play in extracellular electron transfer in Gram-negative bacteria such as Shewanella and Geobacter species (2022). Similar c -type cytochrome electrical contacts have been proposed for Fe(III)-reducing Archaea such as Ferroglobus and Geoglobus species (23, 24). However, the study of the mechanisms for extracellular electron transfer in these archaea has been stymied by the lack of microorganisms available in pure culture that can grow via extracellular electron transfer and are genetically tractable.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…The putative function of outer-surface cytochromes is terminal electron transfer to extracellular electron acceptors, similar to the role that outer surface c -type cytochromes play in extracellular electron transfer in Gram-negative bacteria such as Shewanella and Geobacter species (2022). Similar c -type cytochrome electrical contacts have been proposed for Fe(III)-reducing Archaea such as Ferroglobus and Geoglobus species (23, 24). However, the study of the mechanisms for extracellular electron transfer in these archaea has been stymied by the lack of microorganisms available in pure culture that can grow via extracellular electron transfer and are genetically tractable.…”
Section: Introductionsupporting
confidence: 64%
“…A wide diversity of archaea are capable of extracellular electron transfer (72), but the mechanisms are poorly understood. For archaea such as Ferroglobus placidus (23), Geoglobus ahangari (24), and diverse ANME (1319) it has been proposed that outer-membrane cytochromes are the terminal reductase. The rapid non-physiological reduction of extracellular electron acceptors by a range of redox-active proteins and co-factors in vitro necessitates genetically tractable model organisms for physiologically relevant functional studies.…”
Section: Resultsmentioning
confidence: 99%
“…An exception to this formed MPEBLZ_02042 which had many homologs in the bacterial and archaeal domain albeit with only moderate sequence identity (= 37%). Homologs that were found for many of the other proteins comprised proteins from the Fe(III) reducing Euryarchaeota Ferroglobus placidus and Geoglobus acetivorans (Mardanov et al, 2015 ; Smith et al, 2015 ). The sequence identity was generally low and spanned only part of the protein (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results suggest that these proteins might form extracellular conductive structures or pili as in Shewanella or Geobacter . Here, periplasmic, outer-membrane, or pilus-bound Cytc transfer electrons to and from the cells (reviewed for example in Gorby et al, 2006 ; Richter et al, 2012 ; Boesen and Nielsen, 2013 ; Smith et al, 2015 ). This might provide a structural and biochemical basis of the metal ion-reducing and the presumed electron-conductive capabilities of the iron-metabolizing Archaea.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, many heme-stained bands were found SDS gels of extracts of Fe 3+ -grown F. placidus cells. The number of bands and of transcripts of Cytc genes differed depending on the solution state of the iron: there were more Cytc proteins and corresponding transcripts in cells grown on solid compared to soluble Fe 3+ species; in addition there were numerous type IV pili suggesting close attachment of the cells to the substrate and/or electrically conductive pili (Smith et al, 2015 ). By analogy, the sulfate reducer Archaeoglobus veneficus with a total of 16 Cytc genes should also be able to grow by metal respiration (Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%